AKUNTANSI BAHAN SISA STONEWARE BSK-4 PADA PRODUKSI ASBAK COKLAT (D 11,0 CM – T 5,5 CM) - I Nyoman Normal; Wiryawan Suputra Gumi (STIMI Handayani Denpasar, 2015)
The aims of this research were: (1) To know the cost of goods manufacturedBSK-4 stoneware; (2) To know the accounting treatment of scrap material; (3)To know the influence of accounting treatment of scrap material to cost of goodsmanufactured brown astray; and (4) To know the influence of accounting treatmentof scrap material to net profit margin brown astray. The research results shew that:(1) The the cost of goods manufactured BSK-4 stoneware was Rp 2.633,76 each kg.The BSK-4 stoneware is a work in process goods, because it was an result from production process of quartz, kaolin, Kalimantan clay, RRT feldspar, andit was araw material to produce ceramics goods that is brown astray; (2) The productionprocess of brown astray (d 11,0 cm - h 5,5 cm) based Kalimantan clay create scrapmaterial, that is BSK-4 stoneware about 3% or 0,012 kg. Its scrap material wasnot sold and its creating was caused by its ordering characteristic. The accountingtreatment of BSK-4 stoneware annihilation cost was load on brown astray order,by debit of work in process goods - raw material cost, and credit of raw materialcost; (3) The accounting treatment of scrap material BSK-4 stoneware was influenceof cost of goods manufactured brown astray. Cost of goods manufactured brownastray before accounting treatment of scrap material was Rp 19.801,35, and afteraccounting treatment of scrap material was Rp 19.819,35 each unit, so it wasdecrease Rp 18,00 each unit; and (4) The accounting treatment of scrap materialBSK-4 stoneware was influence of net profit margin brown astray. Net profit marginbrown astray before accounting treatment of scrap material was Rp 2.780,44, andafter accounting treatment of scrap material was Rp 2.784,56 each unit, so it wasdecreaseRp 4,12 each unit.